ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN EFEKTIVITAS KINERJA DAN KEDISIPLINAN KARYAWAN PADA PT ENEGIA TRANSMEDIA DI CABANG DPR RI - Muhamad Wimar Putra Wijaya; Senen (Journal of Research and Publication Innovation, 2024)
PT Energia Transmedia is a company that has been established since 2004, and is engaged in providing labor and supporting machines and vehicles. PT Energia Transmedia's customers consist of various sectors ranging from Government, BUMN and Private. Human Resources (HR) are a vital component in a company, because these individuals are able to carry out tasks, manage operations, and drive the company's progress. To maintain the quality of human resources, leadership style is an important factor in managing each employee to carry out their main tasks and functions in order to achieve company goals. The purpose of this research is to find out and how to analyze leadership styles in improving the effectiveness of performance and discipline of employees of PT Energia Transmedia, DPR RI branch. The type of research used in terms of the location of the data source includes case research and field research. This research approach uses descriptive qualitative. The research was conducted at PT Energia Transmedia using data collection techniques in the form of interviews, observation and documentation. The results of this research show that the leadership style applied by PT Energia Transmedia is an effective democratic leadership style involving clear and open communication. Leaders who are able to convey company goals, provide constructive feedback, and listen to input from employees can build mutual understanding and improve performance. So it can be concluded that the democratic leadership style has a positive impact on employee performance and discipline.